The impact of governing bodies on schools in Northern Province, Region Three - Netshishivhe, F.R. (My University, 2014)
The establishment of democratic governing bodies in schools is one of the requirements of the South African Schools Act, 1996. This study investigates the impact of governing bodies on schools in the Northern Province: Region Three. In doing so, the study examines the role played by the Provincial Education Department, headmasters, teachers and learners in the establishment of democratic governing bodies. It covers six schools from six areas of Region Three in the Northern Province. Through interviewing officials of the Department of Education who are actively involved with school governance, the headmasters of each school visited, parents, teachers and learners, their views and perceptions were examined regarding the role of governing bodies in schools. The researcher also made use of observation to gather information on the work of governing bodies in schools. School environments and the state of buildings were observed as a measure to determine dedication and commitment of the headmasters, staff and members of the governing bodies. Despite all the democratic processes followed in the implementation of school governing bodies, and the new powers and functions that have been given to them, governing bodies have not successfully democratised schools. Neither have governing bodies improved the culture of learning and teaching; contributed to the provision of quality education and curriculum development; helped in the maintenance of discipline, or raised funds for the schools. This study has revealed that factors such as educational resources, time,different interest groups, lack of active participation, differing value systems in the sub-culture and different age groups impact....the activities of governing bodies. The results of the study suggest that there is the need for programmes to train members of the governing bodies into the new ethos, including sacrificing their time; being committed and becoming actively involved in the activities of governing bodies and schools.